Leo L. Beranek and Tim J. Mellow, Acoustics – Sound Fields and Transducers, Elsevier – Academic Press 2012 - Andrzej DOBRUCKI (Archives of Acoustics)
The reviewed book is a new, expanded and modernized edition of the classical position of the book “Acoustics” published in 1954 and reprinted in 1986. The subtitle: “Sound Fields and Transducers” reflects well the nature of the changes in relation to the original. The chapters concerning sound fields and transducers have been added or significantly expanded and chapters on other subjects, such as noise control, hearing, and speech, have been removed. The chapter about acoustic measurements has been also removed, although some parts of it concerning reciprocity calibration of transducers would be compatible with the concept of the present version of the book. The book consists of 14 chapters. The chapters are divided into parts which are numbered consecutively, independently on numeration of chapters, and sections numbered within chapters. The book contains also three appendices. The scientific level of the book is high and it is designed for advanced readers, e.g., graduate students, and professionals who want to expand their knowledge.